Axial compressive behavior of reinforced concrete-filled stainless steel tube (RCFSST) stub columns: Experimental research. (December 2021) - Qiao, Qiyun; Li, Jiafeng; Mou, Ben; Cao, Wanlin
Abstract: In this study, an innovative reinforced concrete-filled stainless steel tube (RCFSST) column is proposed. A total of twenty-two specimens, including eighteen RCFSST stub columns and four concrete-filled stainless steel tube (CFSST) stub columns were tested under axial compression. The primary variables included cross-section type (circular and square), spiral stirrup spacing (spiral stirrup ratio), number and strength of longitudinal reinforcing bars, and concrete strength. The failure modes, load versus deformation curves, ultimate bearing capacity, strain characteristics, local buckling stress, and ductility of the specimens were compared and discussed. Results showed that the load versus deformation curves were stable, and outward buckling was the final failure mode for all specimens. Compared with CFSST columns, RCFSST columns had higher ultimate bearing capacity and better ductility. Increasing the spiral stirrup ratio can significantly improve ultimate bearing capacity and post-peak ductility. Increasing the number and strength of longitudinal reinforcing bars can also increase ultimate bearing capacity. Higher concrete strength can improve the ultimate bearing capacity of the specimen but worsen post-peak ductility. Inserting a reinforcement cage, even a small amount, can be an economical method of significantly improving the ductility of CFSST columns with high strength concrete. Finally, design formulas for calculating the ultimate bearing capacity of RCFSST columns subjected to axial compression loading were proposed. Highlights: ● An innovative reinforced concrete filled stainless steel tube (RCFSST) column is proposed. ● Twenty-two stub columns were tested under axial compression. ● Failure modes, ultimate strength, strain characteristics, local buckling stress, and ductility are investigated. ● Design formulas for calculating the ultimate strength of RCFSST columns are proposed.